THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND WORK COMMITMENT ON TREASHER'S PERFORMANCE WITH REMUNERATION AS AN INTERVENING VARIABLE AT STATE UNIVERSITY OF GORONTALO - Hariani Tanda; Usman Moonti; Niswatin (International Journal of Innovations in Engineering Research and Technology, 2023)
Study This aim For know influence intelligence emotional and committed Work to performance treasurer with remuneration as intervening variables at Gorontalo State University. Deep data source study This is the primary data through deployment questionnaire to 33 Treasurers . Data analysis technique used is analysis path with SPSS version 21 assistance . Research results This show that (1) Intelligence emotional influential positive and significant to remuneration to the Treasurer at Gorontalo State University. (2) Commitment Work influential positive and significant to remuneration to the Treasurer at Gorontalo State University. (3) Intelligence emotional influential positive No significant to performance Treasurer at Gorontalo State University. (4) Commitment Work influential positive No significant to performance Treasurer at Gorontalo State University. (5) Remuneration influential positive and significant to performance Treasurer at Gorontalo State University. (6) Intelligence emotional through remuneration influential positive and significant to performance Treasurer at Gorontalo State University. (7) Commitment Work through remuneration influential positive and significant to performance Treasurer at Gorontalo State University.